Community marriage initiatives - Doherty, William J.; Anderson, Jared R. (My University, 2013)
This article reviews the development of community marriage initiatives and their relationship with family professionals, with particular emphasis on sociohistorical context. We describe five leading community marriage initiatives, discuss the state of the evaluation research, and propose new directions for this promising area of work.
Keywords: Marriage; Marriage education; Community; Evaluation